2021
DOI: 10.4103/jfmpc.jfmpc_1632_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on fasting and postprandial lipid profile in type 2 diabetes mellitus

Abstract: Context: Postprandial dyslipidemia plays a vital role in the pathogenesis of atherosclerosis and possible macrovascular complications in type 2 diabetes mellitus (DM). Aims: To assess and compare the fasting and postprandial lipid profiles in type 2 DM patients. Settings and Design: This case-control study was conducted in the Medicine department of a tertiary care teaching hospital. Methods and Materials: The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This present study was designed to validate if the combination of the two therapies can yield a synergetic effect better than their individual effect since, they are readily available and cheap. A lipid profile measures total cholesterol, LDL-C, HDL-C, and triglycerides, all of which can be used to forecast pathological conditions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This present study was designed to validate if the combination of the two therapies can yield a synergetic effect better than their individual effect since, they are readily available and cheap. A lipid profile measures total cholesterol, LDL-C, HDL-C, and triglycerides, all of which can be used to forecast pathological conditions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of serum lipid profile: The following parameters were estimated by using a fully autoanalyzer using kits. 10 (a) Total cholesterol (TC), was estimated by using the CHOD-POD method. (b) Triglycerides (TG) were estimated by the GPO-PAP method.…”
Section: Methods Of Assaymentioning
confidence: 99%
“…Postprandial hypertriglyceridemia is a hallmark of dyslipidemia in patients with type 2 diabetes. Recently, it has been suggested that postprandial dyslipidemia is equally as important as the estimation of lipids in the fasting state, particularly for patients with type 2 diabetes ( 67 ). Mora et al ( 27 ) characterized lipoprotein particles according to size in fasting and non-fasting states by using NMR, noting similar results between LDL and HDL particles.…”
Section: Very-low-density Lipoprotein Particles In the Non-fasting St...mentioning
confidence: 99%